An Overview of Arab Women's Experiences in the Novel Ismi Salma Fadia Faqir's Work: A Gynocritical Study - Azza Shofia Rahmada; Misbahus Surur (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Fadia Faqir's novel Ismi Salma presents a complex narrative about the experience of Arab women who live in exile and identity disconnection in the midst of cultural clashes between Hart and West. Through the character of Salma, Faqir depicts women's struggles in dealing with trauma, patriarchy, and weistence in a foreign land that does not fully accept ber existence. Although this novel har been widely studied from the perspective of diaspora, identity, and trauma, Blaine Showalter's gynocritical approach has never been applied to analyze it. This study was conducted to examine the representation of Arab women's experiences in Ismi Salma's novel and explore the influence of Fadia Fagir's background as a female writer in the construction of female characters and narratives in it. The method used is descriptive qualitative analysis with a gynocritical approach that includes four main models: biology, language, psychology, and female culture. The results show that Fadia Faqir consciously write from a female perspective, rairing bodily experiences, prychological trauma, social alienation, and resistance to patriarchal culture. The character of Salma comet ar a female witness who represents the voice of Arab diasporic women who are marginalized but still trying to redefine bome, identity, and freedom. The implications of this study emphasize the importance of the gynocritical approach in revealing women's narratives from the perspective of women themselves, as well as enriching the study of feminizm in Arab diasporic literary works.